Knowledge and Attitude about Organ Donation and Transplantation among Students of a Medical College in Kalaburagi - Nimra Shireen; Mohammad Waseem Ansari; Amruta S Indupalli; Shibi Selladurai; Shri Srinivas Reddy (Medsci Publications, 2018)
Introduction: Organ donation is a community service, which not only saves lives but also improves the quality of life as well. Although awareness regarding voluntary blood donation is satisfactory among our people, pledging for donation of organs after death lacks prominence in our country. Health care professionals play a vital role in imparting positive knowledge towards organ donation. The study was conducted to assess the knowledge about organ donation and transplantation among medical students and to study their attitudes towards organ donation. Methodology: An Institution based cross sectional study was conducted at ESIC Medical College, Kalaburgi for a period of two months. A pre-tested, semi-structured and self-administered questionnaire was used to collect the data. Data was analyzed by using SPSS version 23. Results: The mean + SD of knowledge score was 11.54 + 2.54 and only 4.5% of the students had good knowledge about organ donation and transplantation. Majority (79%) of them had positive attitude towards organ donation. Conclusion: There exists a wide knowledge gap among the students about organ donation and transplantation, but they have a positive attitude towards organ donation. Therefore, awareness programmes about organ donation and transplantation needs to be organized in the medical colleges across the country.